Endocrine disrupters : hazard testing and assessment methods - Matthiessen, Peter (Hoboken, N.J. : Wiley, 2012)
"This book describes methodology and applications for endocrine disrupter toxicity testing, an issue of considerable urgency, because of international regulatory authorities currently considering such testing schemes. The coverage examines major animal groups for sensitivity to endocrine disrupting chemicals (EDCs), identifying endpoints and procedures for testing guidelines. Three EDC screening methods (two using fish and one using amphibians) are examined in detail for their efficacy and applicability. Edited by, and with contributions from, a leading participant in regulatory efforts, the book outlines methods that combine sensitivity, efficiency, statistical power, acceptable cost, and minimum ethical concern"--
"This book examines major animal groups for sensitivity to endocrine disrupting chemicals (EDCs), identifying endpoints and procedures for chemical industry and regulatory authority testing guidelines. The emphasis is on practical testing methods that combine sensitivity, efficiency, statistical power, acceptable cost, and minimum ethical concern. Three EDC screening methods (two using fish and one using amphibians) that have recently been standardized and published as Test Guidelines by OECD are covered, and these will be examined in detail for their efficacy and applicability"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Endocrine disrupting chemicals -- Toxicity testing; Endocrine disrupting chemicals -- Environmental aspects; Endocrine toxicology; SCIENCE -- Chemistry -- Industrial & Technical; Electronic books; Electronic books